2024
DOI: 10.1021/acs.joc.3c02452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Lewis Acid-Catalyzed Cycloaddition of Bicyclo[1.1.0]butanes with Ketene: Bicyclo[1.1.0]butanes Serving as an Electrophile

Dan Liu,
Xuefeng Guo,
Shaoyuan Zhou
et al.

Abstract: Lewis acid-catalyzed cycloaddition between bicyclo[1.1.0]butanes (BCBs) and unsaturated substrates has recently been demonstrated to be a powerful strategy for synthesizing bicyclo[2.1.1]hexanes. However, their reaction mechanisms remain elusive. This computational work explored the recently developed TMSOTf-catalyzed cycloaddition of BCB ketone to ketene and determined the rate-determining step as the activation of BCB ketone. Contrary to the previous proposal of BCB enolate as the active species, this work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Interestingly, Zhang and coworkers conducted a computational investigation into this reaction mechanism and suggested that a Lewis acidactivated BCB ketone acts as an electrophile for a ketene nucleophile (right panel of the proposed mechanism). [51] Regardless of the exact mechanism of cycloaddition, Studer and coworkers demonstrated a broad scope of ketenes and BCB ketones including alkyl BCB ketones 158 and 159. However, BCB esters and amides only provided trace product, presumably due to a less electrophilic BCB to either TMSOTf activation or the ketene nucleophiles.…”
Section: Polar Cycloadditions To Construct Bchsmentioning
confidence: 99%
“…Interestingly, Zhang and coworkers conducted a computational investigation into this reaction mechanism and suggested that a Lewis acidactivated BCB ketone acts as an electrophile for a ketene nucleophile (right panel of the proposed mechanism). [51] Regardless of the exact mechanism of cycloaddition, Studer and coworkers demonstrated a broad scope of ketenes and BCB ketones including alkyl BCB ketones 158 and 159. However, BCB esters and amides only provided trace product, presumably due to a less electrophilic BCB to either TMSOTf activation or the ketene nucleophiles.…”
Section: Polar Cycloadditions To Construct Bchsmentioning
confidence: 99%
“…Subsequent nucleophilic addition of imidazolidine/hexahydropyrimidine 2 / 3 to the carbocation center of intermediate II forms ammonium species III . Importantly, it is obviously different from the pioneering precedents by Leitch and co-workers, Studer and co-workers, and Glorius and co-workers that triggered the reaction with nucleophilic attack from the anion moiety of intermediate II (path b in Scheme B) . Subsequent aminal ring opening affords zwitterionic iminium species IV , followed by intramolecular cyclization to afford the target product 4 / 5 with the release of the B(C 6 F 5 ) 3 catalyst.…”
mentioning
confidence: 99%